Ovarian follicle growth dynamics during the postpartum period in Holstein cows and effects of contemporary cyst occurrence - Rajmon, R.; Šichtař, J.; Vostrý, L.; Řehák, D. (Czech Journal of Animal Science, 2012)
The indicators of follicle development with regard to the growth wave order, the first ovulation, animal parity, and also with regard to the simultaneous presence or absence of a follicular cyst were determined in cows in the course of 60 days postpartum. Follicular dynamics were monitored daily by ultrasonography. The animals were assigned to three groups based on the time of the 1st ovulation: G1 (n = 9) - the 1st dominant follicle (DF) ovulated, G2 (n = 10) - ovulation occurred on the 2nd or later follicular waves, and G3 (n = 5) - no ovulation occurred during the experimental period. G1 animals showed better fertility later (no cyst, less days open, P = 0.07, less hormonal treatment, P = 0.008). The rhythm of follicular wave development was generally similar in all the animals (based on emergence of the first follicular wave, the interval from emergence to deviation, and the number of all follicular waves). Nevertheless, emergence of follicular waves and deviation occurred by 0.5-0.9 day earlier in primiparous than in multiparous cows and in G1 vs. G2, or G3, respectively (in all P < 0.05). DF development was independent of parity as well as group effects, but the maximum size and growth rate (1.2 vs. 0.8 cm/day, P < 0.05) were higher in ovulatory follicles (OF) than in regressive ones (rDF). The presence of a growing cyst decreased the probability of rDF as well as OF development (P < 0.0001). The OF growth rate was faster in the milieu of a stagnating cyst than without any cyst (P < 0.04). Therefore, the development of follicles was dramatically suppressed beyond, but nor before, deviation in the milieu of a growing cyst. Cessation of the cyst growth accelerated the development of OFs. On the contrary, a cystic structure without any significant growth can persist for weeks with no effect on successful follicular development.
Keywords: cow; postpartum; ovary; follicular wave; dominant follicle; cyst